RESEARCH ON EFFECTS OF RATE OF BECKOSOL 6501-80 AND SOLID POWDER TO PROPERTIES OF ALKYD PAINT SURFACE FILM OF WOOD - Thi Vinh Khanh, Nguyen; Van Chu, Tran; Trong Kien, Nguyen; Quoc An, Cao (Journal of Forestry Science and Technology, 2017)
The alkyde paint has high gloss, hardness, and flexibility, good color retention of coating film. It is good for adhesion with wood, metal and others. However, there have been very few researches on alkyde paints in Vietnam recently. This paper is aimed at studying the influence of rate of Beckosol 6501-80 binder and solids powder as titanium oxide R, Lithopone, CaCO3 to quality of surface film of Alkyde paint. The result was showed as follows: when the rate of 6501-80 alkyd binder changed from 35% to 45%, and the rate of solods powder changed from 15% to 20% , the surface adhesion of paint reached level 1,2 and 3, depending on the composition ratio; hardness reached level 1H and 2H; Bending strength reached level 1; Dry surface time reached 2.5 to 2.8 hours, the complete drying time reached from 19 to 21 hours; The gloss of alkyd paint reached range from 72 to 75; The acid bases resistance reached level 70 to 84%. The mechanical and physical properties of alkyde paint film reached the highest quality when the rate of binder is at 45% of total input volume, but quality of paint film of 15% solid powder is better than that of 20%. However, this difference is not very significant, so the rate of binder and solid using for wood reached the most suitable level is 45% and, solids powder is 20% of total input volume.